ROLE PLAY IN MARKET DAY FOR STIMULATION EARLY CHILDHOOD SOCIAL EMOTIONAL - Fikri, As’syifa Nur; Jazariyah; Andri Hardiyana (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2024)
The development of children’s social and emotional abilities is essential for supporting their future quality of life. Efforts to develop these abilities can be made through various activities that are engaging for children. The aim of this study is to understand the development of children’s social and emotional skills, to describe the implementation of role-playing methods using the market day technique on children’s social and emotional development, and to identify the challenges faced by teachers in applying the role-playing method. This study uses a qualitative descriptive approach. The subjects of this study are students and teachers at TK PGRI Tanjungkerta. Data were collected using observation, interviews, and documentation methods, with data analysis consisting of data reduction, data presentation, and conclusion drawing. The instruments used in this study are interview guidelines and observation sheets. The results of the study show that the application of the role-playing method using the market day technique on social and emotional development yielded an average score of 86.41% with the criteria of developing as expected (BSH) https://ppid.bnn.go.id/. In the implementation of the role-playing method, teachers followed the predetermined steps. The challenges faced by teachers included a lack of assistant teachers and limited time. However, these challenges were successfully managed. The results of this study can be used as a reference in efforts to develop social and emotional skills in early childhood.